Pengaplikasian Motif Busana Dayak Ngaju Menjadi Busana Ready To Wear - Linda Utami; Sunarmi Sunarmi; Arif Jati Purnomo; Afifah Nur; Nabila Khoirunisa (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2025)
Indonesia is rich in art and culture, one of which is the Dayak Ngaju tribe in Central Kalimantan with their traditional clothing full of symbolism, such as the Enggang and Kalalawit motifs. This research aims to transform Dayak Ngaju traditional clothing into ready-to-wear clothing for cultural preservation and promotion. Using the Design Thinking method, the process begins with understanding the philosophy of traditional attire (Empathize), identifying the needs of young people for comfortable and stylish traditional attire (Define), then conceptualizing ideas for simplifying motifs on modern materials using painting techniques (Ideate), and finally creating prototypes (Prototype). Testing results showed positive responses to the design, which blends modernity with authenticity, deemed attractive, boosting confidence, and potentially becoming a trend. However, constructive feedback was received regarding material comfort (polyester that feels hot), motif proportions, garment cuts (sleeves and collars), and the durability of the painting after washing. Further development is recommended in terms of size variations and formal touches. With this approach, it is hoped that the Dayak Ngaju adaptation clothing can preserve culture dynamically, promote innovation, empower the community, and open economic opportunities.